Lumbopelvic fixation and sacral decompression for a U-shaped sacral fracture: case report Fixação lombopélvica e descompressão sacral para fratura em U do sacro: relato de caso - Marcelo D. Vilela; Charles Jermani; Bruno P. Braga (Arquivos de Neuro-Psiquiatria)
BACKGROUND: U-shaped sacral fractures are highly unstable, can cause significant neurological deficits, lead to progressive deformity and chronic pain if not treated appropriately. OBJECTIVE: To report a case of a U-shaped sacral fracture treated with lumbopelvic fixation and decompression of sacral roots in a 23-years-old man. METHOD: Decompression of the sacral roots combined with internal reduction and lumbopelvic fixation using iliac screws. RESULTS: Restitution of lumbosacropelvic stability and recovery of sphincter function. CONCLUSION: Lumbopelvic fixation is effective in restoring lumbosacralpelvic stability and allows full mobilization in the postoperative period. Good neurological recovery can be expected in the absence of discontinuity of the sacral roots. INTRODUÇÃO: As fraturas sacrais em U são instáveis e podem causar significativa lesão neurológica, deformidade progressiva e dor crônica se não tratadas apropriadamente. OBJETIVO: Relatar caso de um homem de 23 anos com fratura em U do sacro tratada com fixação lombopélvica e descompressão das raízes sacrais. MÉTODO: Descompressão da cauda equina associada a redução interna e fixação lombopélvica usando parafusos ilíacos. RESULTADOS: Reconstituição da estabilidade lombosacropélvica e recuperação da continência esfincteriana CONCLUSÃO: A fixação lombopélvica é eficaz em restaurar a estabilidade lombo-sacro-pélvica e permite mobilização imediata no pós-operatório. Recuperação neurológica pode ser esperada na ausência de neurotmese das raízes sacrais.